Tautomeric Equilibria in Solutions of 2-Phenacylbenzimidazoles - Agnieszka Skotnicka; Przemysław Czeleń; Ryszard Gawinecki (Heteroatom Chemistry)
Detailed NMR spectral analysis of DMSO-d6 solutions of the series of substituted 2-phenacylbenzimidazoles (ketimine form, K) reveals two from three tautomeric forms. Integrals of the 1H NMR signals are used in establishing the molar ratio of tautomers. The experimental analyses are supported by quantum-chemical calculations, which satisfactorily reproduced the experimental trends. Although the reported semiempirical quantum-chemical calculations show that enaminone E, i.e., 2-(1,3-dihydro-2H-benzo[d]imidazol-2-ylidene)-1-phenylethan-1-one, was thermodynamically most stable, the results of MP2 ab initio calculations reveal the following order of stability: ketimine > enolimine > enaminone (substituents do not affect this sequence). 13C CPMAS NMR spectral data reveal that in the crystalline state the enolimine tautomer O is predominant in the p-CH3 and p-NO2 substituted congeners.